KUALITAS PELAYANAN PROGRAM LARASITA (LAYANAN RAKYAT UNTUK SERTIFIKAT TANAH) DI BADAN PERTANAHAN NASIONAL (STUDI PELAYANAN HAK JUAL BELI DI KECAMATAN PONOROGO) - Mega Rouzana Auliya Rahma; Meirinawati Meirinawati (Publika, 2021)
Larasita (The People's Service for Land Certificates) is one of the innovations in the field of land administration services in accordance with the Regulation of the Head of the National Land Agency of the Republic of Indonesia No. 18 of 2009 concerning Larasita within the Ministry of Agrarian Affairs and Spatial Planning or the National Land Agency. Larasita is a service assistance with a ball pick-up system or mobile service using technology and motorized vehicles. This service uses an online or computerized system so that it is able to transfer and communicate data to servers in each land agency. This study aims to describe in a concretely how the Service Quality of the Larasita Program (People's Service for Land Certificates) at the National Land Agency (Study of Sale and Purchase Rights Services in Ponorogo District) is. The research method used is descriptive research and quantitative approach. This research took a sample of 53 people from a total population of 112 customers using the Accidental Sampling technique. The operational definition of variables, namely through the dimensions of service quality according to Hardiyansyah (2011), includes: physical evidence, reliability, responsiveness, assurance and empathy. Data collection techniques include interviews, questionnaires, observation and documentation. Meanwhile, the data analysis method used descriptive quantitative analysis. The results showed that the tangible indicator/physical evidence obtained a percentage of 77.92%, the reliability/reliability indicator obtained a percentage of 81.98%, the responsiveness indicator obtained 75.34%, the assurance indicator obtained 76.69%, and the empathy indicator got 83.69%. Overall, the quality of the Larasita program service (sales for sale and purchase rights services in Ponorogo district) obtained a percentage of 78.91% which was in the "Satisfied or quality service". Keywords: Larasita Program, Buying and Selling Rights Service, Service Quality Larasita (Layanan Rakyat Untuk Sertifikat Tanah) merupakan salah satu inovasi dibidang layanan administrasi pertanahan yang sesuai Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia No. 18 Tahun 2009 tentang Larasita di lingkungan Kementerian Agraria dan Tata Ruang atau Badan Pertanahan Nasional. Larasita adalah bantuan jasa yang bersistem jemput bola ataupun mobile service dengan menggunakan teknologi serta kendaraan bermotor. Pelayanan ini menggunakan sistem online atau komputerisasi sehingga mampu melakukan transfer dan komunikasi data kepada server yang ada di setiap badan pertanahan. Penelitian ini bertujuan guna menjabarkan secara konkret bagaimana Kualitas Pelayanan Program Larasita (Layanan Rakyat Untuk Sertifikat Tanah) di Badan Pertanahan Nasional (Studi Pelayanan Hak Jual Beli di Kecamatan Ponorogo). Metode penelitian yang digunakan yakni penelitian deskriptif dan pendekatan kuantitatif. Penelitian ini mengambil sampel sebanyak 53 orang dari jumlah populasi 112 pelanggan dengan mengenakan teknik Accidental Sampling. Adapun definisi operasional variabel yakni melalui dimensi kualitas layanan menurut Hardiyansyah (2011), meliputi: bukti fisik, kehandalan, responsivitas, jaminan dan empati. Teknik pengumpulan data meliputi wawancara, angket, observasi serta dokumentasi. Sedangkan, untuk metode analisis data menggunakan analisis kuantitatif deskriptif. Hasil penelitian menunjukkan bahwa indikator tangible/ bukti fisik memperoleh presentase sebesar 77,92%, indikator reliability/kehandalan memperoleh presentase 81,98%, indikator responssiveness/daya tanggap memperoleh 75,34%, indikator assurance/jaminan memperoleh 76,69%, dan indikator empathy/empati memperoleh 83,69%. Secara keseluruhan kualitas pelayanan program larasita (studi pelayanan hak jual beli di kecamatan ponorogo) memperoleh presentase sebesar 78,91% yang terletak pada golongan “Puas atau berkualitas”. Kata Kunci: Program Larasita, Pelayanan Hak Jual Beli, Kualitas Pelayanan